Suitability of Sul-Po-Mag as a Potassium Cum Magnesium fertilizer for Banana in Kerala - Anila Mathew (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1997)
The present investigation was carried out in the Department of Soil Science and Agriculture Chemistry, College of Horticulture, Vellanikkara during the period of September 1994 to August 1995. The study was aimed to bring to light the suitability of Sul-Po-Mag as a potassium cum magnesium fertilizer for banana in Kerala. The treatments included Sul-Po-Mag substitutes of potassium to the extend of -25, 50 and 100 per cent in the normal recommended dose of NPK as urea, diammonium phosphate and muriate of potash at the rate of 190 g N, 115 g P205 and 300 g K20 per plant per year. Treatments of muriate of potash supplemented with magnesium and sulphur separately and with magnesium and sulphur together were also included and they were compared with the recommended practice. The experiment was laid out in randomised block design with three replication. During the early stages of growth, the treatments failed to influence the morphological characters such as height, girth and number of leaves of the plant. But at the later stages, the girth and the number of leaves differed significantly and the application of Sul-Po-Mag showed a favourable influence on these characters. No significant difference was observed in characters like total number of suckers, days to flower, days to mature and total duration of the crop among the treatments. Among the bunch characters, numbers of hands, length and girth of fingers and bunch weight were influenced by the difference in treatments while the number of fingers per bunch and weight of fingers remained unaffected. The maximum yield was given by the treatment where potassium was supplied by Sul-Po-Mag and muriate of potash in half doses. Though the treatments differed